Effect of Dietary Supplementation of Protease Enzyme on Performance of Commercial Broiler Chicken - Tripathi, Palak; Patel, Atul B.; Bhagora, Nikesh J.; Savaliya, Fulabhai P.; Mishra, Ram Kailash; Rajpura , Rais M. (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
An experiment was conducted to investigate the effect of dietary supplementation of different levels of protease enzyme with reduced  crude protein (CP) levels of diet on the performance of commercial broiler chicken. Total 160 straight run day-old commercial broiler  chicks were randomly distributed to five treatments, with four replicates consisting of eight birds in each. The treatments were: T1 (Basal  diet as per BIS 2007), T2 (1% CP reduction than basal diet with addition of protease enzyme @ 175 g/ton of feed), T3 (2% CP reduction  than basal diet with addition of protease enzyme @ 175 g/ton of feed), T4 (1% CP reduction than basal diet with addition of protease  enzyme @ 350 g/ton of feed), T5 (2% CP reduction than basal diet with addition of protease enzyme @ 350 g/ton of feed). The data of  body weight, body weight gain, feed consumption, feed conversion ratio, carcass characteristics and economics of rearing of broiler  birds were recorded during the experimental period of 6 weeks. Results indicated that the dietary supplementation of protease enzyme  @ 175 g/ton of feed and @ 350 g/ton of feed with 1% or 2% reduction in CP level of diet showed numerically higher body weight and  weight gain as compared to control. Feed conversion ratio was at par with the control. Carcass characteristics were not affected by  protease enzyme supplementation. However, protease enzyme supplementation @ 350 g/ton of feed with 2% reduction in CP level as  well as 175 g/ton of feed with 1% reduction in CP level in broiler diet resulted in higher economic return (Rs./bird) in terms of return over  feed cost (ROFC). Further study is required with higher levels of protease enzyme supplementation with reduced CP levels of broiler  diets to achieve optimum growth performance of broiler birds.
Keywords: Broiler; Carcass traits; Crude Protein (CP); Growth performance; Protease enzyme